Host Genetics Background Influence in the Intragastric Trypanosoma cruzi Infection - Domingues, Carolina Salles; Cardoso, Flávia de Oliveira; Hardoim, Daiana de Jesus; Pelajo-Machado, Marcelo; Bertho, Alvaro Luiz; Calabrese, Kátia da Silva (Frontiers in Immunology, 2020)
Background: Considering the complexity of the factors involved in the immunopathology of Chagas disease, which influence the Chagas’ disease pathogenesis, anti-T. cruzi immune response and chemotherapy outcome, further studies are needed to improve our understanding about these relationships. On this way, in this article we analyzed the host genetic influence on hematological, histopathological and immunological aspects after T. cruzi infection. Methods: BALB/c and A mice were intragastrically infected with T. cruzi SC2005 strain, isolated from a patient of an outbreak of Chagas disease. Parameters such as parasite load, survival rates, cytokines production, macrophages, T and B cell frequencies and histopathology analysis were carried out. Results: BALB/c mice presented higher parasitaemia and mortality rates than A mice. Both mouse lineages exhibited hematological alterations suggestive of microcytic hypochromic anemia and histopathological alterations in stomach, heart and liver. The increase of CD8+ T cells, in heart, liver and blood, and the increase of CD19+ B cells, in liver, associated with a high level of proinflammatory cytokines (IL-6, TNF-α, IFN-γ), confer a resistance profile to the host. Although BALB/c animals exhibited the same findings observed in A mice, the response to infection occurred later, after a considerable parasitaemia increase. By developing an early response to the infection, A mice were found to be less susceptible to T. cruzi SC2005 infection. Conclusions: Host genetics background shaping the response to infection. The early development of a cytotoxic cellular response profile with the production of proinflammatory cytokines is important to lead a less severe manifestation of Chagas disease.